MEDU-37. NEURONAL DIFFERENTIATION AND CELL-CYCLE PROGRAMS MEDIATE RESPONSE AND RESISTANCE TO BET-BROMODOMAIN INHIBITION IN MYC-DRIVEN MEDULLOBLASTOMA. (23rd April 2019) - Bandopadhayay, Pratiti; Piccioni, Federica; O'Rourke, Ryan; Ho, Patricia; Gonzalez, Elizabeth; Gionet, Gabrielle; Qian, Kenin; Clymer, Jessica; Balboni-Iniguez, Amanda; Lam, Fred; Shapira, Ofer; Greenwald, Noah; et al.
Abstract: BET-bromodomain inhibition (BETi) has shown pre-clinical promise for MYC-amplified medulloblastoma. However, the mechanisms for its action, and ultimately of resistance, have not been fully defined. Using a combination of expression profiling, genome-scale CRISPR/Cas9-mediated loss of function and ORF/cDNA-driven rescue screens, and cell-based models of spontaneous resistance, we identified bHLH/homeobox transcription factors including NEUROD1, NEUROG1 and NEUROG3, and cell-cycle regulators CCND2 and CCND3 as key gene mediators of BETi's response. Furthermore, these genes also mediated resistance, and were re-expressed in cells that acquire resistance to BETi through chronic dosing. Cells that acquired drug tolerance exhibit altered cell state, with an increase in neuronally differentiated cell-state and expression of lineage-specific bHLH/homeobox transcription factors. However, they did not terminally differentiate, maintaining the expression of SOX2 and the capacity to cycle through S-phase, re-instating expression of CCND2. Analysis of human medulloblastomas revealed heterogeneous populations of cell states, including those that expressed both neuronal and stem markers, and would be predicted to be less sensitive to BETi. Barcoding techniques to track evolution of cells through treatment indicated the existence of cells that are predetermined to acquire resistance to BETi. Finally, we found inhibition of cell-cycling with CDK4/CKD6 inhibition to delay acquisition of resistance, providing a rationale for combination treatments. These findings provide insights into the mechanisms of action of BETi as a therapeutic strategy for MYC -driven medulloblastoma that can be leveraged to increase efficacy in the clinical setting.